A vertical-axis rotor as the adjusting system of a horizontal axis wind turbine - Augustyn Marcin (Technical Transactions, 2020)
The proposed self-adjusting mechanism consists of a carousel rotor with a vertical axis consisting of two kinematically connected flat blades. The torque of this rotor can change the position of the directing unit and additionally the position of the main propeller in order to direct the wind stream or save the main rotor when the wind is too strong. The theory, principles of operation, and the properties of the self-adjusting system were illustrated by formulas and graphs. Based on research conducted in a boundary layer wind tunnel, the values of the aerodynamic coefficients of the flat blades were determined, and then the power and propeller torque of the rotor were found as a function of the angle of wind attack. A computational procedure provides kinematical and force relations as well as the resulting torque diagrams of the rotor. An example of the use and the design structure of a self-adjusting unit in the case of a horizontal axis wind turbine is presented.